Journal of Human Sport and Exercise - 2019 - Summer Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc5.37
|View full text |Cite
|
Sign up to set email alerts
|

What determine the innovation performance of Sports SMEs in Thailand?

Abstract: The study can add to the existing literature on SMEs, service innovation, and dynamic capabilities by the identified mechanism. The way in which service innovation can be improved in SMEs has been explained in this research. The managerial and theoretical guidelines have been offered to achieve the competitive advantages based on service. This has been achieved by showing the way in which ACAP (dynamic knowledge capability) can be encouraged through internal and external collaboration. The study has used the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…Subsequently, and based on the results of the learning capabilities (LeC) variable, our study concurs with those of Ali et al. (2017), Kerdpitak et al. (2019), Valaei et al.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Subsequently, and based on the results of the learning capabilities (LeC) variable, our study concurs with those of Ali et al. (2017), Kerdpitak et al. (2019), Valaei et al.…”
Section: Discussionsupporting
confidence: 86%
“…The model in this subgraph proposes to strengthen internal soft abilities before investing money in infrastructure. Its results show that strategic planning and management skills, as internal factors of SMEs, influence business competitiveness.Kerdpitak et al. (2019) found that SMEs could improve their competitiveness if they reinforce the capacity to obtain information from the environment and manage internal knowledge.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations